Safety of increasing protein delivery with an enteral nutrition formula containing very high protein (VHP) and lower carbohydrate concentrations compared to conventional standard (SF) and high protein (HP) formulas. Issue 12 (December 2022) - Ochoa Gautier, Juan B.; Berger, Andrea; Hussein, Raghad; Huhmann, Maureen B.
Summary: Background & aims: Studies demonstrate that caloric restriction in the first seven days in the ICU is safe. The amount of protein that should be delivered, however, is still unclear with clinical trials suggesting mixed results. Despite some capacity to customize the delivery of protein using supplemental modules, protein delivered is best determined by the concentration of protein contained in enteral formula (EF) ordered. This fact provides an opportunity to explore the potential clinical effects of protein delivery and lower carbohydrate intake on clinical outcomes compared with conventional enteral formulas. Methods: Retrospective analysis of clinical outcomes according to the amount of protein delivered in critically ill patients admitted to intensive care units at Geisinger Health System. Results: 2000 encounters (1899 patients) in patients on enteral nutrition were divided into three groups receiving EF with either ≤20% protein (standard formula – SF), 21–25% protein (high protein – HP) or > 25% protein (VHP). Protein intake increased up to day 7 (p < 0.0001). Patients on VHP received more protein than other groups (p < 0.0001). Multivariable regression analysis showed no evidence of harm. In fact, we observed increased mortality with SF and HP formulas at 30-days post-discharge when compared to patients on VHP even when the effects of other variables (including age, BMI, sex, primary diagnosis, diabetes, history of dialysis, ICU days kept NPO) were taken into consideration. Conclusions: Increasing protein intake while reducing carbohydrate intake appears to be safe. Further research aimed at defining a causative effect of increasing protein delivery while reducing carbohydrate load on outcomes is warranted.